In Vitro Antioxidant Activity of Ethanolic Extract of Aerial Parts of Coleus spicatus. Benth - Jaslin Edward, J.; Padmaja, V. (Asian Journal of Chemistry, 2011)
The present study is to evaluate in vitro antioxidant activities of ethanolic extract of aerial parts of Coleus spicatus. Benth by hydroxyl, nitric oxide radical and superoxide anion scavenging activity. Ascorbate was used as the reference compound for hydroxyl, nitric oxide and quercetin was used for superoxide anion scavenging activity. The antioxidant activity of ethanolic extract of aerial parts of Coleus spicatus. Benth was on a concentration dependent manner. The ethanolic extract of Coleus spicatus. Benth was found to have significant antioxidant activity when compared to standard.